Sending money home: Transaction cost and remittances to developing countries - Junaid Ahmed; Mazhar Mughal; Inmaculada Martínez-Zarzoso (The World Economy, 2021)
Reducing the cost of remitting is one of the targets within the 2030 Sustainable Development Goals (SDG 10). A key factor that causes migrants to use informal channels when sending money back home is the high cost of transferring funds through formal channels. This study examines whether and to what extent the reduction in the cost of sending remittances increases the flow of remittances to developing countries, and whether larger amounts are remitted when the cost per transaction decreases (the so-called scale effect). It uses bilateral data on remittance flows and exploits a novel dataset covering transaction costs for 30 sending and 75 receiving countries for the period 2011–2017. A gravity model of remittance flows is estimated using panel data and instrumental variable techniques to address endogeneity issues. We find that transaction cost is a significant predictor of the volume of formal remittances. A 1% decrease in the cost of remitting USD 200 leads to about a 1.6% increase in remittances. This association is robust to the different models and techniques employed. The findings suggest that policies designed to increase formal remittances need to focus on decreasing the cost of remitting through formal channels.
Keywords: 330; bilateral remittances; cost of remitting; developing countries; international migration